Ecological consequences of the desertification process in the agrolandscapes of the Kashkadarya oasis - Suyunov Abdusali; Suyunov Shukhrat; Khushmurodov Farrukh; Suyunov Samaritdin; Omonov Ismoil; Eshboev Bekhzod (BIO Web of Conferences)
This scientific article examines the consequences of entanglement processes in the agro-landscapes of the Kashkadarya Oasis. Special attention is paid to soil degradation, pest infestation, erosion, changes in hydrogeological regimes, and the impact of these factors on the sustainability of agroecosystems. The study identifies the main causes of degradation, including anthropogenic and natural factors such as inappropriate use of land resources, irrigation erosion, rising groundwater levels, climatic changes, and low efficiency of land reclamation systems. Methods of geographic information modeling, landscape analysis, remote sensing, and statistical monitoring are used to assess the dynamics of these processes. The authors propose strategies for sustainable agro-landscape management, including introducing modern irrigation technologies, crop rotation, and measures to restore degraded land and prevent vegetation clearance. Raising environmental awareness among the population and integrating a landscape approach to natural resource conservation is also emphasized. It concludes that comprehensive measures are needed to prevent soil degradation, increase agricultural productivity, and adapt the region to environmental changes.